An analysis of industry readiness and strategic options through relevance tree analysis a case study on AMR adoption - Basilla, Jan C. (University of the Philippines Diliman, 2009)
The study takes some un-expected turns as significant number of the surveys send through professional organization in the south failed to come up with the 50 percent return of survey response. Apparently, the result due were expected last week of September were overtaken by recent events of flash floods brought about Typhoon Odung that cause the high rate of none response among prospective industry respondents. Despite these overwhelming challenges, the study was able to gather success as contingency plans from peers and officemates contact came in to augment the survey respondent up to 40 percent. Even with this turn-out response, the interviews to key personnel from Transco, NGCP, MERALCO and vendor consultant done ahead of the survey supplement the survey results and validate the current landscape of ICEC perspective. The first part of the report will give an overview and history of how the Philippine Electricity Market evolved together with the EPIRA law and the early form of Automatic Meter Reading systems. Then it is followed by objective of the study and its limitations. The succeeding two chapters discuss the theoretical framework of Management of Technology with subtopic Technology Strategy and Technology Adoption process by Everett Rogers (1995). The author also expands the AMR at current technology development which highlight the development on communication and smart meter cross functional integration. Likewise, the tool used on the study "Relevance Tree Analysis" is introduced to give a graphical framework of the study. The last three (3) chapters discuss the study approach and process the survey results and findings. Then enumerate the key questions from the methodology approach interview of the Key personnel mentioned above. Lastly, the analysis of the results which the survey for ICEC outlook confirmed; that AMR system is relevant to their application and is more strategic technology option when added functionality such as DSM and PQ are present in the system as in the case of an AMI. Finally, the conclusion and recommendation which mostly geared towards the agency implementing rules and regulation, has to prove it competent to deliver the WESM objectives.